Pola Pengelolaan Pohon Sialang Oleh Masyarakat Desa Betung Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Sari, Gusmita; Yoza, Defri; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Area surround forest have community’s Betung village, Pangkalan Kuras District Pelalawan regency to have all various of sialang tree. As to various of tree mention between other Shorea sp, Dipterocarpus cofertus Sloot, Artocarpus maingayi, Koompassia excels Taub, Koompassia malaccensis and Gluta aptera. However sialang tree don’t manage in this area surround forest by community. The community more important oil palm of management equal sialang tree of management. This research purpose to know management system of sialang tree with this forest area and compare contribution and out put can from sialang tree of management and oil palm of management using Purpossive sampling technique. Result showed that sialang tree of management and taking honey’s bee don’t treatment again. Because many of sialang tree don’t perch so that produced honey’s bee little. Based on analitycal hierarchy process, sialang tree given contribution and out put more good equal with oil palm. Because to out put can from sialang tree maximum if his work long time equal out put can from oil palm maximum if his work long time and out of cost maximum. Key word : management system, sialang tree, community